Comparison Between Stroke Patients and Normal Persons for Trunk Position Sense and It's Relation to Balance and Gait - Hea-Duck Yang; Chang-beom Kim; Jong-Duk Choi; Young Moon (Korean Research Society of Physical Therapy, 2020)
Background: Stroke patients have reduced trunk control compared to normal people. The ability to control the trunk of a stroke patient is important for gait and balance. However, there is still a lack of research methods for the characteristics of stroke control in stroke patients. Objects: The aim of this research was to determine whether trunk position sense has any relation with balance and gait. Methods: This study assessed trunk performance by measuring position sense. Trunk position sense was assessed using the David back concept to determine trunk repositioning error in 20 stroke patients and 20 healthy subjects. Four trunk movements (flexion, extension, lateral flexion, rotation) were tested for repositioning error and the measurement was carried out 6 times per move; these parameters were used to compare the mean values obtained. Subjects with stroke were also evaluated with clinical measures of balance and gait. Results: There were significant differences in trunk repositioning error between the stroke group and the control group in flexion, lateral flexion to the affected side, lateral flexion to the unaffected side, rotation to the affected side, and rotation to the unaffected side. Mean flexion error: post-stroke: 7.95 ± 6.76 degrees, control: 3.32 ± 2.27; mean lateral flexion error to the affected side: 6.13 ± 3.79, to the unaffected side: 5.32 ± 3.15, control: 3.57 ± 1.92; mean rotation error to the affected side: 8.25 ± 3.09, to the unaffected side: 9.24 ± 3.94, control: 5.41 ± 1.82. There was an only significant negative correlation between the repositioning error of lateral flexion and the Berg balance scale score to the affected side (-0.483) and to the unaffected side (-0.497). A strong correlation between balance and gait was found. Conclusion: The results of this study indicate that stroke patients exhibit greater trunk repositioning error than age-matched controls on all planes of movement except for extension. And lateral flexion has correlation with balance and gait.